2010
DOI: 10.1002/fuce.201000012
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of H2S on the Performance of SOFCs using Methane Containing Fuel

Abstract: In recent years, the interest for using biogas derived from biomass as fuel in solid oxide fuel cells (SOFCs) has increased. To maximise the biogas to electrical energy output, it is important to study the effects of the main biogas components (CH4 and CO2), minor ones and traces (e.g. H2S) on performance and durability of the SOFC. Single anode‐supported SOFCs with Ni–Yttria‐Stabilised‐Zirconia (YSZ) anodes, YSZ electrolytes and lanthanum‐strontium‐manganite (LSM)–YSZ cathodes have been tested with a CH4–H2O–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
80
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 50 publications
(90 citation statements)
references
References 22 publications
10
80
0
Order By: Relevance
“…Oxidized species (such as O*) obtained during CO 2 activation (dissociation) play a significant role during biogas reforming or methane dry reforming; oxidizing CH x species [Eq. (16)] to CH x O* species. Subsequent decomposition of CH x O* species produces synthesis gas [Eq.…”
Section: Transient Reaction Studies: Co 2 Dissociationmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidized species (such as O*) obtained during CO 2 activation (dissociation) play a significant role during biogas reforming or methane dry reforming; oxidizing CH x species [Eq. (16)] to CH x O* species. Subsequent decomposition of CH x O* species produces synthesis gas [Eq.…”
Section: Transient Reaction Studies: Co 2 Dissociationmentioning
confidence: 99%
“…(1)- (8)]. This approach has been employed by researchers to gain useful understanding of mechanistic details and catalytic interactions of CH 4 with Ni/YSZ (nickel/yttria-stabilized zirconia) and similar anodes [16][17][18][19][20]. For example, Triantafyllopoulos and Neophytides [17,21] studied catalytic dissociation of CH 4 on Ni/YSZ at various temperatures, monitoring carbonaceous species deposited as well as their reactivity with H 2 and O 2 .…”
Section: Introductionmentioning
confidence: 99%
“…5 The addition of H 2 S to the fuel inlet gas will affect the reformate gas equilibrium as reported by Rasmussen and Hagen and upon addition of 2 ppm H 2 S the CH 4 conversion degree will be decreased and a fuel utilization of approximately 70% can be expected at the chosen test conditions. 23 OCV was checked before starting the test under current load. It was observed that complete internal reforming was obtained, since OCV values of ∼988-992 mV correspond to the reformed equilibrium gas mixture of H 2 /CO/H 2 O/CO 2 :65.6/15.5/15.6/3.2 (OCV theo.…”
Section: /H 2 O/h 2 Fuel Mixtures At 850mentioning
confidence: 99%
“…As pointed out in the work by RostrupNielsen et al [19], it is still not fully clear how sulfur interacts with Ni active sites in terms of heterogeneous catalytic and electro-catalytic processes respectively. Anyway, sulfur certainly reduces the catalytic activity of Ni in an SOFC cermet anode [20,21]. In [21], authors showed how sulfur strongly reduces Ni reforming activity toward methane more than the electrochemical reactions.…”
Section: Introductionmentioning
confidence: 97%
“…Anyway, sulfur certainly reduces the catalytic activity of Ni in an SOFC cermet anode [20,21]. In [21], authors showed how sulfur strongly reduces Ni reforming activity toward methane more than the electrochemical reactions. For this reason, in a direct internal reforming SOFC configuration, as we are interested in, sulfur should be removed to satisfactory levels that guarantee a proper catalytic activity of the Ni.…”
Section: Introductionmentioning
confidence: 97%